2006
DOI: 10.1111/j.1755-0238.2006.tb00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Grape vine varieties Shiraz and Grenache differ in their stomatal response to VPD: apparent links with ABA physiology and gene expression in leaf tissue

Abstract: Two cultivars of Vitis vinifera L., namely Grenache and Shiraz, have been described as having near‐isohydric and near‐anisohydric responses respectively to soil water stress (Schultz, Plant Cell and Environment, 26, 1393–1405, 2003). Given that contrast in sensitivity to soil water, a question arises as to whether atmospheric moisture stress will elicit similar differences. The present study was undertaken to investigate this issue by comparing stomatal responses in these same two cultivars to contrasting vapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
135
3
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(165 citation statements)
references
References 43 publications
17
135
3
9
Order By: Relevance
“…In order to determine whether these stress treatments were activating ABA biosynthesis in the plant tissues, we examined the key rate-limiting steps in the plant ABA biosynthetic pathway catalyzed by ZEP and NCED (Liotenberg et al, 1999). Previous studies on grapevine leaves have showed that water stress specifically induced VvNCED1 but not VvZEP, and this is associated with an increase in bulk leaf ABA concentrations (Soar et al, 2004(Soar et al, , 2006. Our analysis shows that powdery and downy mildew infection and wounding also led to rapid and significant increases in VvNCED1 expression, but no consistent pattern in VvZEP expression was observed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine whether these stress treatments were activating ABA biosynthesis in the plant tissues, we examined the key rate-limiting steps in the plant ABA biosynthetic pathway catalyzed by ZEP and NCED (Liotenberg et al, 1999). Previous studies on grapevine leaves have showed that water stress specifically induced VvNCED1 but not VvZEP, and this is associated with an increase in bulk leaf ABA concentrations (Soar et al, 2004(Soar et al, , 2006. Our analysis shows that powdery and downy mildew infection and wounding also led to rapid and significant increases in VvNCED1 expression, but no consistent pattern in VvZEP expression was observed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Blackman & Davies (1983) postulated that cytokinins reverse the stomatal closing promoted by aBa application; subsequently, Incoll & Jewer (1985) verified that when kinetin was applied to Anthephorapubescens, stomatal opening was promoted. other proof of cytokinin effects on stomatal movement has also been published (Mansfield & McAinsh 1995;Soar et al 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Generally, anisohydric plants display lower amounts of, or sensitivity to, the stress hormone ABA (Loveys and During, 1984;Loewenstein and Pallardy, 1998;Tardieu and Simonneau, 1998;Soar et al, 2006). Low levels of ABA can lead to high levels of SA due to antagonistic interactions between these two phytohormones (Audenaert et al, 2002; Mohr and Cahill, 2007;de Torres Zabala et al, 2009;Jiang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%